Search for low mass Higgs bosons produced in Z0 decays - Abreu, P; Adam, W; Adami, F; Adye, T; Akesson, T; Alekseev, G; Allen, P; Almehed, S; Alted, F; Alvsvaag, S; Amaldi, U; Anassontzis, E; et al. (1991)
A search for light Higgs bosons was performed using the data sample collected in 1990 by the DELPHI detector at LEP, at centre of mass energies between 88.2 and 94.2 GeV. Using the process e+e-→H0+Z0*, Z0*→ff, it is possible to exclude the existence of the standard model Higgs particle with a mass between 0 and 210 MeV/c2 at the 99% confidence level. Extending this analysis to the minimal supersymmetric standard model restricts the lightest neutral Higgs boson to masses above 28 GeV/c2 irrespective of the value of the mixing angle. © 1991 Springer-Verlag.